Bournout em profissionais de Enfermagem: prevenção e consequências - Tomas, Diego; Soares, Rafael Gomes; da Costa, Gleiciane Nunes; Neves, Rosalia Gabriele; Oliveira , Verônica de Oliveira; Carvalho, Silvia de Souza; Oliveira, Pedro Henrique Moraes; Araújo, Natália da Silva; da Silva, Deborah Sousa; Mendes, Fabíola da Silva; Silva Mangueira de Assis, Emily Suelle; Costa dos Santos, Robert William (Brazilian Journal of Implantology and Health Sciences, 2024)
This article aims to carry out a literature review (RIL) about bornout in nursing professionals because it is a topic that is growing and affects them in different ways, whether in mood, mental health and physical health. The majority of nurses who had burnout syndrome did not practice physical activity. The results found can support the development of relevant points for reflection, such as prevention, detection and behaviors that minimize Burnout syndrome in nursing residents through the training services of institutions promoting this type of teaching-learning specialty. The methodology adopted consisted of original articles, preferably those with case studies, preferably in Portuguese accessed on the SCIELO website.